2003
DOI: 10.1152/ajprenal.00064.2003
|View full text |Cite
|
Sign up to set email alerts
|

Altered dietary iron intake is a strong modulator of renal DMT1 expression

Abstract: Divalent metal transporter1 (DMT1; also known as DCT1 or NRAMP2) is an important component of the cellular machinery responsible for dietary iron absorption in the duodenum. DMT1 is also highly expressed in the kidney where it has been suggested to play a role in urinary iron handling. In this study, we determined the effect on renal DMT1 expression of feeding an iron-restricted diet (50 mg/kg) or an iron-enriched diet (5 g/kg) for 4 wk and measured urinary and fecal iron excretion rates. Feeding the low-iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 29 publications
5
42
2
Order By: Relevance
“…Renal DMT1 is another iron protein that to date has not been studied in depth in hemolytic anemia. Our results showing intense DMT1 expression in medulla in anemia are in agreement with those reported in animals on an iron-restricted diet, a condition of increased iron demand (33). The DMT1 expression observed in inner and outer medulla in healthy mice is similar to that reported by other authors (10,13).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Renal DMT1 is another iron protein that to date has not been studied in depth in hemolytic anemia. Our results showing intense DMT1 expression in medulla in anemia are in agreement with those reported in animals on an iron-restricted diet, a condition of increased iron demand (33). The DMT1 expression observed in inner and outer medulla in healthy mice is similar to that reported by other authors (10,13).…”
Section: Discussionsupporting
confidence: 93%
“…High levels of dietary iron produce an increase in DMT1 expression in hepatocytes, promoting iron acquisition, whereas low levels decrease hepatic DMT1 expression, causing a reduction in iron accumulation (26,32). Although kidney is not usually associated with serum iron balance, several studies found renal DMT1 expression in mice and rats, suggesting that this organ may have a role in iron homeostasis (4,10,33). Furthermore, Wareing et al (34) reported a decrease in urinary iron levels, suggesting iron reabsorption in renal tubules.…”
mentioning
confidence: 99%
“…Interestingly, four DMT1 isoforms have been identified in renal tissue (19). Thus the difference between the effects of Zn 2ϩ action on Cd 2ϩ uptake in the LH and more distal segments could be due to the pattern of expression of these different isoforms (33).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of the mutated DMT1 molecule in neurons suggests that the low cerebral iron uptake in b/b rats derives from a reduced neuronal uptake rather than an impaired iron transport through the blood-brain barrier (Moos & Morgan, 2004). Kidney studies remain to show the importance of DMT1 as well as different isoforms (Abouhamed et al, 2006;Canonne-Hergaux & Gros, 2002;Wareing et al, 2003;. Pharmacokinetic studies show that iron status can alter lung Mn transport to circulation Heilig et al, 2005;Thompson et al, 2006) DMT1 is not the transporter involved .…”
Section: Divalent Metal Transporter (Dmt1) In Mn Transportmentioning
confidence: 99%